2020
DOI: 10.1002/mbo3.975
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and characterization of the predicted diguanylate cyclase‐encoding genes in Pseudomonas aeruginosa

Abstract: Opportunistic pathogen Pseudomonas aeruginosa can cause acute and chronic infections in humans. It is notorious for its resistance to antibiotics due to the formation of biofilms. Cyclic‐di‐GMP is a bacterial second messenger that plays important roles during biofilm development. There are 40 genes in P. aeruginosa predicted to participate in c‐di‐GMP biosynthesis or degradation. It is time‐consuming for the functional characterization of these genes. Here, we cloned 16 genes from P. aeruginosa PAO1 that are p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 41 publications
1
7
0
1
Order By: Relevance
“…Except for PA2818 ( arr ), the fluorescence intensity of stationary phase culture is higher than that of the exponential phase culture (Figure 2A), which is consistent with the stability of Gfp. According to previous publications (15, 75), the two key DGCs, SadC and SiaD showed stronger effects on intracellular c-di-GMP concentration than other DGCs of P. aeruginosa , yet our results indicated their transcriptional level was relatively low among DGCs (Figure 1). We then selected five genes, PA0169 ( siaD ), PA2818 ( arr ), PA4332 ( sadC ), PA4601 ( morA ), and PA4843 ( gcbA) , to detect their transcription by qRT-PCR.…”
Section: Resultssupporting
confidence: 65%
See 1 more Smart Citation
“…Except for PA2818 ( arr ), the fluorescence intensity of stationary phase culture is higher than that of the exponential phase culture (Figure 2A), which is consistent with the stability of Gfp. According to previous publications (15, 75), the two key DGCs, SadC and SiaD showed stronger effects on intracellular c-di-GMP concentration than other DGCs of P. aeruginosa , yet our results indicated their transcriptional level was relatively low among DGCs (Figure 1). We then selected five genes, PA0169 ( siaD ), PA2818 ( arr ), PA4332 ( sadC ), PA4601 ( morA ), and PA4843 ( gcbA) , to detect their transcription by qRT-PCR.…”
Section: Resultssupporting
confidence: 65%
“…A systemic tool will be a great help for a deep understanding about how P. aeruginosa regulates the 41 CMR genes in response to various environmental temperatures, signals and antibiotics. A few reports have focused on the comprehensive and systemic features of those c-di-GMP related genes or proteins in bacteria (15,17,(59)(60)(61)(62), while those studies are mainly focused on the functions of genes or enzymes. Therefore, a systemic transcriptional profile of the 41 CMR genes in P. aeruginosa remains lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Regulation of bacterial motility by c-di-GMP is complex. Low levels proved to be beneficial for this trait, whereas either artificial accumulation or removal of c-di-GMP resulted in motility inhibition (Abel et al 2011;Bhasme et al 2020;Pallegar et al 2020;Yang et al 2016).…”
Section: C-di-gmp-mediated Regulation Of Motilitymentioning
confidence: 99%
“…Yet previous studies of c-di-GMP networks in PA14 (Kulasakara et al, 2006;Ha et al, 2014) or another PAO1 strain (Bhasme et al, 2020) have shown a drastic effect on motility-related behaviors (Figure 10). This re-emphasizes the importance of deciphering the impact that individual members of c-di-GMP networks may have in different P. aeruginosa strains, e.g., PA14 and PAO1.…”
Section: Discussionmentioning
confidence: 70%